Swedish - Finnish glossary: election - Swedish-Finnish glossary: election - Language Council of Sweden, Institute for Language and Folklore (Institute for Language and Folklore, 2020)
Swedish - Finnish glossary of words relating to election and voting. Contains 94 entries. Published in Kieliviesti 1/2006.

Svensk-sverigefinsk ordlista med ord och begrepp som rör val och att rösta. Publicerades i Kieliviesti 1/2006. Innehåller 94 uppslagsord. 2006.
Svensk-finsk ordlista: valbegrepp
Keywords: elections; val; referendums; folkomröstningar; electoral systems; valsystem; election campaigns; valkampanjer; Linguistics; Språkvetenskap; word list; ordlista; national election; nationellt val; Language and linguistics; Språk och lingvistik; Languages and Literature; Språk och litteratur; Comparative Language Studies and Linguistics; Jämförande språkvetenskap och allmän lingvistik